2009
DOI: 10.1097/ede.0b013e31819e370b
|View full text |Cite
|
Sign up to set email alerts
|

Are Nested Case-Control Studies Biased?

Abstract: It has been recently asserted that the nested case-control study design, in which case-control sets are sampled from cohort risk sets, can introduce bias (“study design bias”) when there are lagged exposures. The bases for this claim include a theoretic and an “empirical evaluation” argument. Both of these arguments are examined and found to be incorrect. Appropriate methods to explore the performance of nested case-control study designs, analysis methods, and compute power and sample size from an existing coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…There has been some recent debate in the literature about study design bias in nested case-control studies [21]. However, methodological flaws discussed concern mainly analysis of lagged exposure data, which is not the case in the investigated association (ie, pRBC transfusion and ICUacquired BSIs).…”
Section: Limitations Of Our Studymentioning
confidence: 99%
“…There has been some recent debate in the literature about study design bias in nested case-control studies [21]. However, methodological flaws discussed concern mainly analysis of lagged exposure data, which is not the case in the investigated association (ie, pRBC transfusion and ICUacquired BSIs).…”
Section: Limitations Of Our Studymentioning
confidence: 99%
“…In this study, no bias was observed when a simple random sample of controls was selected from the risk set for each case identified using attained age alone. 15 Hein et al 16 simulated occupational cohorts with time-dependent exposures to evaluate incidence-density sampling in the presence of exposure lagging. In these simulations, exposure effect estimates from analyses that matched on attained age alone were unbiased, and, in lagged analyses, including lagged-out cases and controls (assigned zero lagged exposure) did not introduce bias.…”
Section: Discussionmentioning
confidence: 99%
“…Risk-set sampling in conjunction with exposure lagging was evaluated by Langholz and Richardson 15 in a simulation study based on the Colorado Plateau uranium miners cohort. In this study, no bias was observed when a simple random sample of controls was selected from the risk set for each case identified using attained age alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levy and colleagues32 proposed that controls sampled from age-based risk sets should be matched on the age at date of last observation in order to correct a supposed ‘imbalance’ between cases and controls. Theoretical considerations33 34 question this new matching criterion, and empirical simulations12 35 implementing it have found that it produces a notable downward bias in risk estimates. Wacholder36 notes that traditional risk set sampling is expected to produce unbiased results, even when exposure lagging is used.…”
Section: Discussionmentioning
confidence: 99%